Dialogism in detail: Per Linell's Rethinking language, mind, and world dialogically and its potentials. (September 2013) - Lourenço, Pedro; Basto, Isabel; Cunha, Carla; Bento, Tiago
Per Linell's (2009) book Rethinking language, mind, and world dialogically offers an integrated view upon the many strands of Dialogism, establishing itself as an essential reference to the field. In this review of his book we aim to discuss a few selected topics, building upon these with our own views. Initially, we focus on the relevance and urgency of such book by summing up the most important dialogical concepts presented by it. Following our initial argument, we move on to the discussion of contrasts between monological and dialogical perspectives, the concepts of extended mind and the interworld, suggesting Dialogism as an ontology, and finally, reflecting upon the relation between intersubjectivity and alterity. We conclude our review by stressing how Linell's book contributes to the unification of an entanglement of different dialogical theories and perspectives, crafting a solid meta-theory. This integration paves the way for a deeper understanding of what constitutes the nature of knowledge and human phenomena, as conceptualized by Dialogism.